Prediction of early reperfusion from repeated arterial spin labeling perfusion magnetic resonance imaging during intravenous thrombolysis - Okazaki, Shuhei; Griebe, Martin; Sauter-Servaes, Johannes; Wolf, Marc; Gass, Achim; Hennerici, Michael G.; Szabo, Kristina; Kern, Rolf (Stroke, 2016)
Background and Purpose: There are few in vivo data on the pathophysiology of reperfusion during systemic thrombolysis. We monitored the time course of cerebral perfusion changes in patients during thrombolysis with repeated arterial spin labeling perfusion magnetic resonance imaging. Methods: Ten patients with proximal arterial occlusion within 4.5 hours after symptom onset were prospectively enrolled. All patients received intravenous thrombolysis during the magnetic resonance imaging examination. Repeated arterial spin labeling perfusion images were acquired during the 60-minute therapy and at follow-up after 24 to 72 hours. Clinical data, magnetic resonance imaging features, and cerebral perfusion changes were analyzed. Results: Before thrombolysis, arterial spin labeling hypoperfusion and fluid-attenuation inversion recovery vascular hyperintensity in the territory of the occluded arteries were observed in all patients. In 5 patients, extensive arterial transit artifacts (ATA) developed in the hypoperfused area. The ATA corresponded with fluid-attenuation inversion recovery vascular hyperintensities. All 5 patients who developed extensive ATA in the hypoperfused area had complete reperfusion after thrombolysis, whereas the 5 without extensive ATA showed no or only partial reperfusion (P<0.01). The development of ATA preceded the normalization of tissue perfusion. Conclusions: The development of ATA during thrombolysis is associated with early reperfusion after thrombolysis. arterial spin labeling assessment during intravenous thrombolysis has the potential to guide subsequent therapeutic strategies in patients with acute stroke.
Gesehen am 16.01.2019